Resilience as a Modulating Factor of Empathy in Medical Students - Acosta-Martínez , Adán A.; Sandoval , Mildred A.; Monterroza, Leida G.; Reyes-Reyes, Fernando; Reyes-Reyes, Alejandro; Vilca, Lindsey W.; Díaz-Narváez, Víctor (Medicina Clínica y Social, 2024)
Introduction: Empathy is a complex and multidimensional attribute. Attempts have been made to explain empathic behavior based on other variables. Empirical evidence shows that empathy could be the product of the influence of several factors. One of these factors could be resilience. There is still no developed theory and consistent empirical evidence demonstrating that empathy depends on resilience. Objective: The aim of this study is to determine if resilience can predict empathic behavior. Methodology: This study is non-experimental and ex post facto with a cross-sectional design. Variables. Dependent: Empathy; Independent: Resilience. Population: Medical students belonging to the Faculty of Health Sciences of the Universidad Autónoma de Santa Ana (UNASA), Santa Ana, El Salvador (N=579). The sample (n=465) consisted of students (both sexes). Convenience sampling. Jefferson Scale of Empathy for Healthcare Professionals, student version (JSE-HPS). Trait Resilience Scale (EEA). A Structural Equation Modelling (SEM) model was used. Additionally, the Comparative Fit Index (CFI) (>0.95), Tucker-Lewis Index (TLI) (>0.95), Root Mean Square Error of Approximation (RMSEA) (<0.08), and Standardized Root Mean Square (SRMR) (<0.08), Confirmatory Factor Analysis (CFA) were employed. The significance level employed was ? < 0.05. Results: All these results show that both measurement models (empathy and resilience) are adequately represented and are suitable for the structural model. Discussion: Individual resilience is a variable that can predict empathic behavior in medical students belonging to a Faculty of Health Sciences. The results constitute indirect empirical evidence that it is possible to define empathy as a dependent variable and resilience as an independent variable.